Antibacterial Activity Test of Mangosteen Plants (Garcinia Mangostana L.): A Review - Andani, Rika; Fajrina, Anzharni; Asra, Ridho; Eriadi, Aried (Asian Journal of Pharmaceutical Research and Development, 2021)
Background: Bacterial infection was a health problem thathard to overcome, due to the presence of bacterial resistance to current antibacterial drugs. Therefore, the use of herbal antibacterials is an alternative that can be used. Mangosteen (Garciniamangostana L.) is a plant that contains xanthone compounds and its derivatives have antimicrobial, antioxidant, cytotoxic, anti-inflammatory, and anti-HIV activity.Part of the mangosteen was used as a medicinal plant such as bark, fruit peel, fruit, seeds, and leaves.This review aimed to determine the antibacterial effectiveness of the mangosteen and inhibitory diameter that was resulting. Data Collection: The author was created this article review by conducting literature studies. The works of literature were collected from national and international journals in the last ten years (2010-2020) and pharmaceutical scientific books. The works of literature were collected from trusted online journal sites such as the digital library, PubMed, PubChem, ScienceDirect, NCBI, Elsevier, NCBI, Researchgate, Google Scholar, Springer, and other trusted E-resource with the keyword "mangosteen”, “Garcinia mangostana L”, “antibacterial activity”, and “inhibitor zone”. Result: According to literature showed that the mangosteen fruit peel, bark, leaves, seeds and fruit effective as antibacterialfor several types of bacteria. Conclusion:N-hexane that was extracted from mangosteen peel has potential as an antibacterial activity at a concentration of 15.62 mg/ml and inhibit the growth of Staphylococcus aureus ATCC25923 with an inhibitory diameter of 17mm.